ВАЛЕНТНОСТНЫЕ ПАРТНЁРЫ ПРИЛАГАТЕЛЬНОГО - Байниязова, С.Т. (SCIENCE and SOCIETY, 2016)
This article is devoted to the valence partners of adjectives. Author notes, the participle with adjectives combine those that have the same obligatory valence partners: they are definable subjects. In attributive use, the adjective comes after definable subjects but in predicative- it becomes subject-matter of predicative construction. Author showed the peculiarities of adjective valence with many examples.
Keywords: adjective; actants; distribution; nominative; valency; accusative actant; obligatory actant; syntactical valency; meaning; teaching; knowledge